COMPETENCY-BASED APPROACH IN HIGHER EDUCATION: A MYTH AND REALITY - Vasiliy S. Senashenko; T. B. Mednikova (Moscow Polytechnic University, 2016)
In this article some objective difficulties are analyzed, which arise when higher education system is proceeding to the implementation of the major educational programs according to the competency-based FGOS VPO. The imperfection of its constructive component is pointed out, when solving didactic problems of Russian higher education. Some distinctive features of competencies in US higher education are discussed. Some significant differences оf the approaches to their implementation in Russian and US higher education systems are indicated.